Desenho, história e memória do nego fugido: contribuições para contextos educacionais - Sousa, Jamilson Oliveira de (2023)
This document presents the results of a qualitative research in the interdisciplinary area, in which it is possible to identify theoretical reflections that involve intercessory knowledge in the fields of social sciences and arts. During this research, we sought to investigate what are the methodological processes in Drawing, History and Memory, of the cultural manifestations of Nego Fugido. Through an anthropological visit, with resources from photography, ethnography, documentary research, theoretical reference survey and interviews. In the text of this dissertation, reflections on racism, on education, on Afro-Brazilian culture and on the contributions of Nego Fugido's Cultural Manifestation Design for educational contexts are developed. As main theories, this text addresses discussions about signs, from Roland Barthes (1964), about the sharing of the sensitive, from Jacques Rancière (2005), in addition to references from several other authors, which strengthened the main discussions of this text, and made part of the literature review of the research. Image analysis appears in this text as a fundamental element for establishing discussions, and, while dealing with this issue (the images), some methodologies are created that can contribute to the application in teaching and learning practices about Afro-Brazilian History and Memory.